1995
DOI: 10.1111/j.1365-2818.1995.tb03678.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in secondary electron imaging

Abstract: SUMMARY Some recent experimental and theoretical developments in secondary electron (SE) imaging are reviewed. Coincidence experiments identify inner‐shell excitations and single electron valence excitations often as more significant initial events in SE production than the more delocalized process of plasmon generation. Quantitative measurement and interpretation of escape depths in different materials are now becoming possible. Local variations in surface barrier height or work function can be imaged, e.g. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Castell et al 5 and Perovic et al 6,7 suggested that this phenomenon is due to surface band-bending. Howie 8 and Sealy et al 9 proposed that local external electric fields called patch fields are important for doping contrast. Patch fields can exist outside a semiconductor specimen due to charge variations on the surface.…”
Section: Introductionmentioning
confidence: 98%
“…Castell et al 5 and Perovic et al 6,7 suggested that this phenomenon is due to surface band-bending. Howie 8 and Sealy et al 9 proposed that local external electric fields called patch fields are important for doping contrast. Patch fields can exist outside a semiconductor specimen due to charge variations on the surface.…”
Section: Introductionmentioning
confidence: 98%
“…Over the last decade attention has been devoted to direct secondary electron (SE) imaging of dopants [2][3][4][5][6][7][8][9][10][11][12][13]. The contrast between the p-and n-type semiconductor (mostly silicon) was found to reach as much as 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Even after liquid water has been removed from a specimen surface, many materials can retain several layers of physisorbed water. It has been postulated that the local organization of these water molecules could alter the escape depth of secondary electrons, giving rise to unusual contrast effects (Howie, 1995).…”
Section: Implications For Imagingmentioning
confidence: 99%